Durian truffles - Abdul Karim, Muhammad Shahrim; Ab Halim, Norhasmilaalisa (University Putra Malaysia, 2012)
Malaysians have been enjoying durian for many generations. Besides eating them fresh, durian can be made into traditional dishes as well as modern dishes. The combination of durian and chocolate in making ‘durian truffles’, for instance, has somehow signified a modernised feature of a gourmet food product. The application of durian in truffles (a ganache which consists a mixture of chocolate and fresh cream) as western dessert origin is viewed as new discovery resulted from the amalgamation of ‘East meet West’ culinary. Durian truffles manifest authentic luxury in a localized chocolate product due to the rich durian flavour mixed with cream and combined with a mixture of cooking chocolate forming a smooth velvety texture. Durian truffles as a product of culinary refinement are ideally served as petite four for cocktail parties.